2020
DOI: 10.1108/jcom-05-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the information diffusion of tweets of a non-profit organization that targets female audiences: an examination of Women Who Code's tweets

Abstract: PurposeThere is a growing interest in the way non-profit organizations can use Twitter strategically to communicate their message, but little attention has been paid to the way content categories and features may facilitate retweets of messages of a non-profit organization that targets women as its audience. Based on stakeholder theory, this study aims to fill this gap by analyzing Women Who Code (WWC)'s tweets to examine whether there are any differences in the number of retweets with respect to the content c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“… Marino & lo Presti, (2018) examined the content of tweets of European Commissioners and proposed a retweetability rate to measure citizen engagement based on the content on social media in response to certain events. Chung et al, (2020) collected the tweets from Women Who Code (WWC) over a one-year period to examine whether certain content and features such as hashtags and photos resulted in differences in retweet volume. Rao et al, (2020) studied the alarming vs. reassuring retweet distribution pattern related to Covid-19.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Marino & lo Presti, (2018) examined the content of tweets of European Commissioners and proposed a retweetability rate to measure citizen engagement based on the content on social media in response to certain events. Chung et al, (2020) collected the tweets from Women Who Code (WWC) over a one-year period to examine whether certain content and features such as hashtags and photos resulted in differences in retweet volume. Rao et al, (2020) studied the alarming vs. reassuring retweet distribution pattern related to Covid-19.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results in literature have suggested that NPOs use SNSs mainly for spreading information (Gao, 2016;Zhou and Pan, 2016;Qu, 2020). While some studies have shown the difference in SNS messages by culture (Waters and Lo, 2012) and emergency situations (Olson et al, 2019), a larger body of literature had reached a similar conclusion that one-way delivery of information was the dominant reason that NPOs use SNSs (Chung et al, 2020).…”
Section: Analysis Of Nonprofit Organizations' Social Media Postsmentioning
confidence: 99%
“…Social media platforms (e.g. Facebook and Twitter) have become an increasingly prominent space for nonprofits to facilitate two-way communication with the public via interactive and dialogic features (Brubaker and Wilson, 2018;Cho et al, 2014;Chung et al, 2020;Wang and Yang, 2020). Recent statistics show that more than half of those who engaged with NPOs on social media ended up supporting the organizations in some way, and 18% of donors worldwide used Facebook fundraising tools to make donations (Nonprofit Source, 2018).…”
mentioning
confidence: 99%
“…Furthermore, social media has great potential to amplify the social impact of nonprofits by facilitating public engagement and building nonprofit-public relationships and social change (Saffer et al, 2019). Thus, the nonprofit sector has increasingly adopted social media as a communication channel (Campbell and Lambright, 2020;Chung et al, 2020;Xu and Saxton, 2019;Young, 2017;Wang and Yang, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation